Determinants in laser-assisted deformed α decay - Cheng, Jun-Hao; Zhang, Wen-Yu; Xiao, Qiong; Deng, Jun-Gang; Yu, Tong-Pu (Physics letters. B, 2024)
Laser manipulation of nuclear decay has extremely promising applications. In this study, cutting-edge Gaussian lasers were combined with the latest data on α decay to thoroughly investigate the factors that impact the penetration probability in laser-assisted α decay of nuclei, while considering the deformation of the nucleus. Our calculations reveal that using state-of-the-art laser fields can marginally alter the half-life of α decay by affecting the penetration probability within a narrow range. Moreover, our findings demonstrate two key points: (1) By deriving an analytical formula for the rate of change of the α decay penetration probability in an ultra-intense laser field, we unveil the negative correlation between the α decay energy and the rate of change of the α decay penetration probability. (2) We attribute the wavelength as the determinant of the effect of the average rate of change of the penetration probability, which we explain by reconstructing the laser pulse width and wavelength. This research offers a rapid method to estimate the rate of change of the α-decay penetration probability and serves as a valuable reference for future experimental investigations of laser-nuclear interactions.